2018
DOI: 10.1590/1984-70332018v18n1a6
|View full text |Cite
|
Sign up to set email alerts
|

Performance of transgenic and conventional soybean plants subjected to bioassay for detection of glyphosate tolerant seeds

Abstract: The adoption of genetically modified soybean cultivars is increasing annually around the world, which indicates the excellence of these genotypes. For soybean breeding, the use of such cultivars in a backcross program relies on the ability to detect the transgenic trait. The germination test in a moistened substrate with glyphosate is effective and of low cost, however, wonders whether this is a non-destructive method to check cultivars. The objective of this study was to apply a bioassay for detection of herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The results of our experiments showed that the data obtained for the various characteristics were within the range observed for soybeans, with the lowest value observed for oil content (4.28%), and the highest for dry matter (51.18%). With the exception of dry matter, the estimated values of the evaluated characteristics were within the CV range observed for soybean (7,11,19,21,26). The highest selective accuracy was verified for flowering and maturation and the lowest for dry matter, conforming to the lowest precision observed for the latter characteristic.…”
Section: Resultssupporting
confidence: 69%
“…The results of our experiments showed that the data obtained for the various characteristics were within the range observed for soybeans, with the lowest value observed for oil content (4.28%), and the highest for dry matter (51.18%). With the exception of dry matter, the estimated values of the evaluated characteristics were within the CV range observed for soybean (7,11,19,21,26). The highest selective accuracy was verified for flowering and maturation and the lowest for dry matter, conforming to the lowest precision observed for the latter characteristic.…”
Section: Resultssupporting
confidence: 69%
“…Analyzing the first and the final counts of germination data (Table 1), it was notable that both herbicide solutions (0.06, and 0.12 %) inhibited the development of normal seedlings by the genotypes, like observed also by Bervald et al (2010) and Pereira et al, (2018). In the case of glyphosate-tolerant cultivars, the highest concentration of the herbicide (0.12 %) affected the first and the final counts of germination, as observed by Pereira et al, (2018), however, the glyphosate-tolerant seedlings developed secondary roots, while the sensitive ones did not (Figure 1). The absence of secondary roots in glyphosate-sensitive seedlings is a striking feature of this bioassay (BERVALD et al, 2010;MELO;FAGIOLI;SÁ, 2013;PÁDUA et al, 2012).…”
Section: Germination Testmentioning
confidence: 86%
“…According to Funguetto et al (2004);Heinz;Viegas Neto and Valente (2011);Pereira et al 2018;and Tillmann and West (2004) the length reductions are more striking for glyphosate-sensitive genotypes. In our study, this was a notable occurrence.…”
Section: Seedling Length Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiation methods based on morphological characters, have the disadvantage of being laborious, time-consuming and influenced by the environment (Shao et al 2010, Orroño andVesprini 2018); in other cases, the expression of transgenes is analyzed directly in seedlings (Pereira et al 2018). An alternative is the characterization with molecular markers.…”
Section: Introductionmentioning
confidence: 99%